Analisis Perputaran Kas, Perputaran Persediaan Dan Perputaran Piutang Terhadap Profitabilitas di PT. Anugerah Kagum Karya Utama Tbk Yang Terdaftar Pada Bursa Efek Indonesia. - MS, Abdul Rasyid; Rahmarisa, Faty; Siregar, Eka Wirandaputri (Universitas Islam Islam Sumatera Utara, 2023)
This research aims to determine the influence of cash turnover, inventory turnover, and account receivable turnover to the profitability (ROA) of manufacture companies which are listed in Indonesia Stock Exchange. The sample collection technique is performed by using purposive sampling technique. Based on the chosen criterion, it draws 36 companies. The type of data is secondary data carried by documentary method which is conducted by accessing websites http://www.idx.co.id/perusahaan-Tercatat/Laporan-Keuangan-dan tahunan/ websites of each company. The data analysis technique is multiple linier regression analysis.The findingsshow that: (1) There is a significant negative influence between cash turnover to the profitability of the company, showed by equation Y= -1,948 – 0,236X1 with value of coefficient of cash turnover regression is -0,236, coefficient of determination (r2) is 0,080, and value tcount -3,519 ttable 1,976. (2) There is no significant positive influence between inventory turnover to the profitability of the company, showed by equation Y = 0,103 + 0,006X2 with value of coefficient of inventory turnover regression is 0,006, coefficient of determination (r2) is 0,001, and value tcount 0,452 ttable 1,976. (3) There is a significant positive influence between account receivable turnover to the profitability of the company, showed by equation Y = 0,042 + 0,032X3 with value of coefficient of account receivable turnover regression is 0,032, coefficient of determination (r2) is 0,077, and value tcount 3,450 ttable 1,976. (4) ) There is a significant positive influence between cash turnover, inventory turnover , and account receivable turnover to the profitability of the company, showed by equation Y = 0,062 – 0,019X1 + 0,005X2 + 0,044X3 with value of coefficient of account receivable turnover regression is 0,236, coefficient of determination (r2) is 0,108, and value Fcount 6,765 Ftable 1,976